Professionalism of law enforcement agencies specialists': theoretical analysis of the problem - Bondarenko, Natalia; Skalenko, Petro (Psychological Prospects Journal, 2022)
Purpose of the article is to present results of the theoretical study of the problem of professionalism of law enforcement specialists.Methods. Theoretical: theoretical and methodological analysis of the current state of the research problem; systematization and generalization of scientific literature on the research problem.Results. Being a qualitative characteristic of the subject of work, professionalism should reflect high professional qualification and competence, a variety of effective professional skills and abilities, including creative solutions, mastery of modern algorithms and ways of solving professional problems. The specifics of tactical and investigative activities makes high demands on both professional skills and personal qualities of law enforcement specialists. A true professional must have a high level of professionalism, have a high professional and social status, a system of personal and activity regulations, dynamically developing, constantly aimed at self-development and self-improvement, personal and professional achievements of social and positive significance. A three-component structure of professionalism of law enforcement specialists has been presented. The cognitive component is expressed by the system of knowledge acquired by the individual about the essence of professionalism and its consciousness; knowledge of norms and rules governing the professional activities of law enforcement specialists; and understanding the content of professional tasks and responsibilities (professional consciousness). Motivational-affective component is characterized by an individual system of motives and meanings of socially responsible behavior; emotional experiences that regulate professional activity (professional morality and ethics; formed a system of values); professionally important qualities of a specialist (professional responsibility, internality of locus control) and its consciousness. Activity-behavioral component is manifested in choice and implementation of certain behaviors and actions in professional situations (ability to quickly solve typical professional problems; ability to be creative, predict, find optimal and effective solutions in unusual situations; ability to communicate with participants).Conclusions. As a result of the theoretical research, the structure and content of the professionalism of law enforcement specialists has been determined. The analysis has also allowed us to make a definition of "professionalism of the law enforcement specialists" as an integrative dynamic characteristic of the subject of activity, including cognitive, motivational-affective and activity-behavioral components dictated by the specifics of the subject and goals of professional activity.